Prospective Associations between Sport Participation and Indices of Mental Health across Adolescence - Graupensperger, Scott; Sutcliffe, Jordan; Vella, Stewart A (My University, 2021)
Youth sport offers physical and psychosocial components that may be beneficial for adolescents' mental health, but the prospective directionality between sport participation and mental health has not been clearly established. The current study examined longitudinal associations between sport participation (individual and team sport) and mental health indices (depressive symptoms, anxiety symptoms, emotional symptoms, hyperactivity symptoms, conduct problems, peer problems, and prosocial behavior) across adolescence (ages 12-17) in a nationally representative Australian sample of 3956 participants at T1 (Mage = 12.41 years, SD = 0.49; 49% female), 3537 at T2 (Mage = 14.41 years, SD = 0.49; 49% female), and 3089 at T3 (Mage = 16.46 years, SD = 0.51; 49% female). Using random intercept cross-lagged panel modeling, several significant within-person effects were found. Notably, greater participation in team sport prospectively predicted fewer symptoms of depression and anxiety at subsequent timepoints. This study increases the understanding of how sport participation may relate to mental health among adolescents and provides critical evidence to inform policy.
Journal of Youth and Adolescence
Keywords: Anxiety; Athletes; Depression; LSAC; Longitudinal; Wellbeing; Health and wellbeing; Lifestyle